Analysis of socio-economic impact of Konkola Copper Mine (KCM) on the mining community in Zambia : a case study of Chingola Town - Kangongo, Dominic (2008)
This thesis focuses on the impact of Konkola Copper Mine (KCM). This company is a Multinational Mining Corporation. It is based in Chingola town in Zambia. The study seeks to establish whether the Mining company is contributing to the development of the town or not. It also examines the development agreements which the company entered into with government and show how this commitment has affected the company’s contributions to the local community. Specifically, the study seeks to critically examine the development agreements with a view to establishing whether these agreements emphasized strict observance of corporate social responsibilities or not The methodological approach used in this study was mainly qualitative which was basically participatory and descriptive; however, this approach did not prevent the use of quantitative approach which was necessary in validating the arguments. The methods used included interviews, observations and review of research and media reports. Theoretical literature was used to develop the framework of the thesis. Study findings demonstrated that the multinational corporation has been actively involved in implementing developmental programmes in Chingola, notable among them is malaria roll back programme, HIV/AIDS, as well as running schools for the community. However, due to weaknesses in the development agreements and legislations, the company has not been able to make significant contributions to the community. Notable among the company’s failures include inconsistence in meeting its financial obligations to the government through corporate tax, royalties and dividends. For example, the study findings showed that the company pays royalties at a rate which is lower than the internationally set rate. Other failures include the repeated pollution of the environment.